Defying challenges: mid-term outcomes of international collaborations for a successful heart transplantation program in the middle east. (25th November 2020) - Hamour, I.M; Ferrer, R; Atallah, B; Gabra, G; Soliman, M; Sabbour, H; Bader, F
Abstract: Introduction: Heart transplantation (HTx) is a successful treatment strategy for advanced heart failure. Survival rates exceed those achieved by medical therapy alone. Lack of suitable donors and cultural perception remain obstacles for receiving this novel therapy. Methods: Overcoming challenges we adopted a first-of-a-kind multicenter HTx program, collaborating between Cardiac Centers in India and the United Arab Emirates (UAE). Patients were worked up as part of our newly established HTx program in the UAE, then referred to India for successful HTx. All post HTx follow-up care was continued in the UAE thereafter. Results: We assessed 10 HTx recipients, [90% male; mean age 34 yrs]. Five patients required inotropes while one LVAD support pre transplant. Our data outline short waiting-list time and excellent 3 years clinical outcomes. All patients are maintained on Tacrolimus and Mycophenolate Mofetil. Two patient developed acute rejection (celluar and humoral) with graft dysfunction within 18 months. Seventy percent had non-ischemic cardiomyopathy pre-transplant. Three acquired donor transmitted coronary vascular disease. One patient developed aggressive allograft vasculopathy requiring coronary artery bypass grafting. Acute kidney injury requiring renal replacement therapy occurred in 1 patient. Conclusion: Defying logistic challenges, donor availability and long HTx waiting list times, we have established a successful multi-center new concept HTx program with excellent mid-term outcome result. Diverse genetic background is evident in the presence of early coronary vascular disease in young donor hearts, requiring extra care in donor screening. This international collaboration has a promising future for new programs in the Middle East. Funding Acknowledgement: Type of funding source: None